Vesicocutaneus fistula after cesarean section-a curious complication: Case report and review - Tatar, Burak (Turk J Obstet Gynecol, 2016)
Vesicocutaneous fistulas are very rare pathologies in the urinary tract. We present the second case of a vesicocutaneus fistula after cesarean section, and discuss strategies for prevention, diagnosis, and treatment of this exceptional complication. A woman with a vesicocutaneous fistula after cesarean delivery was admitted and diagnostic tests including fluoroscopy, magnetic resonance imaging (MRI), and reconstructed MRI revealed the fistula tract and an urachal anomaly. The patient was treated through excision of the fistula tract. Laparotomy should be performed carefully, and the surgeon should be aware of the urachus. Inadvertent trauma to the urachus during laparotomy might cause serious unexpected complications. Possible etiologic factors for vesicocutaneous fistulae, prevention, and treatment methods are discussed.